The Influence of Youtube as a Classical Guidance Media on Student Learning Motivation during the Covid-19 Pandemic - Jannah, Khuzaimatul; Baqiyatussolihat, Babay; Vernandes, Reni (Bisma The Journal of Counseling, 2021)
This study aims to determine the influence of YouTube as a classical guidance media on learning motivation in students during the COVID-19 pandemic. This experimental research uses Posttest Only Control Group Design. The research population is students of 1st grade SMP 3 Kragilan. The research sample consisted of 40 students through random sampling technique, 20 students were the experimental group and 20 students were the control group. Data collection in this study used a questionnaire. The data in this study were analyzed by independent samples t-test using SPSS 16.0 for Windows. The results of the study obtained t count of 2,329, found t table at a significance level of pada (0.05) of 2,021, which means t table < t count. These results prove that YouTube as a classical guidance media has an influence on student learning motivation during the COVID-19 pandemic. Classical guidance media used youtube has several advantages over other classical guidance service media, by using youtube as a learning media, students are more interested and enthusiastic in participating in classical guidance services